Cyclophosphamide with or without fluorouracil followed by subcutaneous or intravenous interleukin-2 use in solid tumors: A feasibility off-label experience. (January 2019) - Lo Re, Giovanni; Lo Re, Francesco; Doretto, Paolo; Del Conte, Alessandro; Amadio, Maria; Cozzi, Cinzia; Casarotto, Maria Maddalena; Maruzzi, Daniele; Marus, Wally; Ubiali, Paolo; Sandri, Paolo
Highlights: Importance of immunosuppressive Treg and MDSC on tumor progression. Immunosuppression of Treg and MDSC cells by Cyclophosphamide and Fluorouracil can improve IL-2 activity. Efficacy of chemo-immunotherapy in pre-treated resistant tumors. Abstract: Background: Immune tolerance seems to correlate with disease progression and T regulatory cells (Tregs) and myeloid-derived suppressor cells play a relevant role in immunosuppression. Cyclophosphamide (Cyt) and Fluorouracil (FU) seem to reduce these cell populations. Methods and objective: Establishing safety, feasibility, activity and impact on the immune system (neutrophil/lymphocyte [N/L], platelet/L [Plt/L], monocyte [M] and lymphocyte subpopulation (CD3, CD4, CD8, CD16, HLADR/CD3, Tregs, cells count), CD8/Treg and C-reactive protein (CRP). Treatment: 1) Cyt 300 mg/sqm ± FU 500 mg/sqm day (d) 1 and interleukin 2 (IL-2) 18 MUI/sqm intravenous (I.V.) d 4–6, 18–20 or 2) Cyt 300 mg/sqm + FU 500 mg/sqm day d 1, IL-2 4.5 MUI subcutaneous (S.C.) d 3–6, 17–20. The cycle was repeated every four weeks for 2 cycles. Stable or responding patients (pts) continued therapy for 3 cycles. Results: From February 2014 to December 2016, 13/14 pre-treated pts (mean 3 lines) with solid tumors were enrolled. Male/Female: 1/1. The median age and Eastern Cooperative Oncology Group Performance Status (ECOG PS) was 68 years and 1 respectively. Mean 2 cycles of therapy were administered. G3-4 toxicities presented as diarrhea and bleeding anemia in 2 pts and proteinuria and erhytroderma in 1pt, respectively. Regarding the hematological profile, a more reduction in Plt, less decrease of Plt/Ly, and less increase of Treg with I.V. than S.C. IL-2 administration was observed. However a transient decrease of Treg on day 7 of first cycle in the I.V. IL-2 was reported. Response: PR 3 (23%), SD 3 (23%), PD 7 (54%). The response duration was 2+ and 3 months in 2 HCC and 18+ months in the pancreatic cancer (PC). Pathological CR was reported in one HCC treated with I.V. IL-2. The median progression-free-survival (PFS) and overall survival (OS) were 1 and 7 months. Conclusion: Cyt-FU-IL-2 can be considered safe, feasible and moderately active in heavily pre-treated pts. Plt, Plt/Ly, CD8/Treg and a transient Tregs reduction were observed without significative difference on survival.